Visualizing the invisible: the kaleidoscopic image and the procedures associated with multiple and connective visuality (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
The current context, characterized by the liquid nature of network-culture, can be categorized as kaleidoscopic. This article presents how the kaleidoscopic image structure was essential in the pre-internet era, with the connective software of the artist Agnes Denes. Her ideas, related to the visualization of the invisible, are somewhat reminiscent of current procedures such as the Event Horizon Telescope for visualizing black holes, where the flow of images is the protagonist.
Keywords: Kaleidoscopic image; visuality; Liquid image; network-culture; Black hole